2021
DOI: 10.1149/2162-8777/ac08d6
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Silicon Film Chemical Vapor Deposition Using Boron Trichloride, Dichlorosilane and Monomethylsilane Gases

Abstract: A boron-silicon film was formed by chemical vapor deposition at 800 °C and atmospheric pressure using boron trichloride, dichlorosilane and monomethylsilane gases. With the increasing boron trichloride gas flow rate at the fixed dichlorosilane gas flow rate, the deposition rate and the boron concentration decreased and saturated, respectively, following the rate theory assuming the Langmuir-type model. The obtained film was amorphous and dense without any voids. The monomethylsilane and the silicon hydrides, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Figure 11 shows a high resolution TEM image of the same film as that of showing a slightly different contrast from the substrate and the main body of the film, similar to a previous study [18]. Figure 11 simultaneously shows that there are no voids in the obtained film.…”
Section: Film Qualitysupporting
confidence: 70%
“…Figure 11 shows a high resolution TEM image of the same film as that of showing a slightly different contrast from the substrate and the main body of the film, similar to a previous study [18]. Figure 11 simultaneously shows that there are no voids in the obtained film.…”
Section: Film Qualitysupporting
confidence: 70%
“…The interaction of fluorouracil (FU) with the quasi-planar B 36 cluster was studied in 2017 [115] using the hybrid TPSSh functional with the 6-31 + G (d) basis set. The FU drug failed to generate any noticeable signal owing to the very weak interaction of this drug with the concave and convex surface of B 36 ranging from −2 to −5 kcal/ mol.…”
Section: Drug Delivery Applicationmentioning
confidence: 99%
“…Boron adsorption occurs at a temperature lower than 800°C, the deposition occurs at 900-1000°C, and at a temperature higher than 1000°C, they observe etching behavior due to chlorosilanes that occur in gaseous form. In their further research in 2021 [115], they reported using a similar boron gas source at 800°C. The etching does not occur on the surface based on the HRTEM result that demonstrated the dense film without void.…”
Section: Current Development Of Boron Cvd Dopingmentioning
confidence: 99%
“…Additionally, this approach can regulate the thickness of Si easily. Silicon nanomembranes (SiNMs) [170] in 2D systems, silicon nanowires (SiNWs) [171] in 1D systems, and silicon nanoparticles [172] in 0D systems can be generated by a bottom-up approach. However, achieving precise manipulation of nanoscale components demands sophisticated techniques and equipment.…”
Section: Introductionmentioning
confidence: 99%